2015
DOI: 10.3233/rnn-140421
|View full text |Cite
|
Sign up to set email alerts
|

Potential determinants of efficacy of mirror therapy in stroke patients – A pilot study

Abstract: Background: Mirror therapy (MT) was found to improve motor function after stroke. However, there is high variability between patients regarding motor recovery. Objectives: The following pilot study was designed to identify potential factors determining this variability between patients with severe upper limb paresis, receiving MT. Methods: Eleven sub-acute stroke patients with severe upper limb paresis participated, receiving in-patient rehabilitation. After a set of pre-assessments (including measurement of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(65 citation statements)
references
References 47 publications
0
58
0
7
Order By: Relevance
“…Whether the stroke types or different lesion sites of patients (e.g., mirror neurons affected or not) influence the treatment efficacy of the action observation therapy or mirror therapy will need to be investigated in the future. In addition, early studies found that the initial motor function of stroke patients was a significant predictor or a critical determinant of motor recovery after receiving rehabilitation therapies [49][50][51]. Whether the baseline severity of the upper limb motor deficits of the patients affects the treatment efficacy of the action observation therapy and mirror therapy needs to be further investigated.…”
Section: Variablesmentioning
confidence: 99%
“…Whether the stroke types or different lesion sites of patients (e.g., mirror neurons affected or not) influence the treatment efficacy of the action observation therapy or mirror therapy will need to be investigated in the future. In addition, early studies found that the initial motor function of stroke patients was a significant predictor or a critical determinant of motor recovery after receiving rehabilitation therapies [49][50][51]. Whether the baseline severity of the upper limb motor deficits of the patients affects the treatment efficacy of the action observation therapy and mirror therapy needs to be further investigated.…”
Section: Variablesmentioning
confidence: 99%
“…In contrast, no change in wrist motor function was observed. Brunetti et al, in 2015 conducted a study to deter- This study concluded that the base level of voluntary movement is one main factor that affects potential motor recovery after MT [20]. As the participants in our study had very minimal voluntary movement in the wrist, we can interpret it as a potential reason for this result in their wrist motor function.…”
Section: Discussionmentioning
confidence: 56%
“…278 The cortical activation in the precuneus region in stroke patients was linked to mirror therapy, and it could be used to determine the e±cacy of the therapy. 279 In a longitudinal study, revascularization surgeries performed on stroke patients resulted in improvements as compared to the levels before surgery, the CBF Fig. 10.…”
Section: Hand/¯nger Movement Taskmentioning
confidence: 98%